Idealistic Philosophy ('I') as Thing-in-itself as Spaceship and Timelessness - Fransisko, Yakub; Melan; Sirnawati; Yappo, Yohanes; Rosen, Imelda; Mariani, Evi; Munte, Alfonso (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2024)
The purpose of this study is merely to examine the philosophy of idealism that seems to be self-oriented (thing-in-itself in/or I) or as if narcissistic anthropocentric and the source of the problem of evil is evil as the logical consequence as the stigma, but when it unfolds in education, whether it be Christian education or education management, it itself then becomes signified, interpreted and signaled. Qualitative research with data search techniques through secondary sources presents various philosophical perspectives as an overview while talking about the philosophy of idealism from Emmanuel Kant, Cartesian, Martin Heidegger, and Quentin Meillassoux through various journals related to researchers' searches. Results show that the philosophy of idealism that departs from the self (thinking, chatting and crossing) becomes spatial constructs in education, including Christian religious education or in researchers' discipline, namely Christian education management.